SELEKSI PENERIMA BANTUAN SOSIAL MENGGUNAKAN METODE FUZZY AHP - Yonhendri; Ahmad Zulfan; Mhd Sandi Rais; Mohd Iqbal; Rezi Elsya Putra (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2022)
The high level of poverty in Indonesia encourages the government and social institutions to seek to provide social assistance to the community in improving welfare, especially during the COVID-19 pandemic, in the form of basic necessities, cash, and other forms of subsidies. However, sometimes the distribution of social assistance is not well-targeted so that some people should receive the assistance but are not touched at all. Then the data obtained are also still manual so it takes time in making decisions. Therefore we need a method that can assist in making decisions quickly with the help of computers. One of the methods used in making these decisions is the Fuzzy Analytic Hierarchy Process (FAHP) which is widely used for solving decision-making problems with many criteria. Fuzzy AHP itself is a combination of the analytic hierarchy process (AHP) method and fuzzy theory. In this study, several criteria were determined in the selection of recipients of social assistance, namely employment, expenditure, clothing, food, and housing. Furthermore, the alternative recipients of social assistance that will be selected are compared based on predetermined criteria. The highest value which is the result of Fuzzy AHP calculations can be used as a recommendation for decision-makers in selecting social assistance recipients. Keywords: fuzzy, ahp, decision support system.